Public responses to atrocities depend on partisanship and context, not legal labels - Yphtach Lelkes; Ellie M. Mitchell; Erin Walk; Sean J. Westwood (Proceedings of the National Academy of Sciences, 2026)
Legal labels such as genocide and crimes against humanity carry substantial legal and diplomatic weight in elite and institutional arenas, where classification shapes treaty obligations, ICC jurisdiction, and the perceived stakes of inaction. A common assumption in advocacy and policy discourse is that these labels also shape mass public judgment. Direct evidence is limited and ambiguous. We test this assumption in a preregistered, nationally representative survey experiment ( N = 2 , 000 ) comparing four legally salient atrocity terms—genocide, war crimes, crimes against humanity, and ethnic cleansing—against a nonlegal control across five real-world conflict contexts, measuring support for punitive and humanitarian policies as well as moral attributions of responsibility. Across outcomes, estimated label effects are small and rarely distinguishable from zero. Critically, even within a given partisan and country context, swapping legal labels produces smaller shifts than the baseline gaps across partisan and geopolitical contexts—indicating that where you stand and who you are matter far more than what word is used. Any departures from zero are narrow and do not accumulate into a consistent pattern across outcomes or conflicts. These results suggest that the political significance of atrocity labeling lies primarily in elite and institutional arenas; for mass publics, legal terminology is a weak lever compared to country context and partisan commitments.